Rebels within the ranks psychologists' critique of scientific authority and democratic realities in New Deal America - Pandora, Katherine 1958- (Cambridge University Press, 1997)
During the 1930s, psychologists Gordon Allport, Gardner Murphy, and Lois Barclay Murphy emerged from the fields of social and personality psychology to challenge the neo-behavioralist status quo in American social science. Willing to experiment with the idea of 'science' itself, these 'rebels within the ranks' contested ascendent conventions that cast the study of human life in the image of classical physics. Drawing on the intellectual, social, and political legacies of William James' radically empiricist philosophy and radical Social Gospel theology, these three psychologists developed critiques of scientific authority and democratic reality as they worked at the crossroads of the social and the personal in New Deal America. Appropriating models from natural history, they argued for the significance of individuality, contextuality and diversity as scientific concepts as they explored what they envisioned as the nature of democracy, and the democracy of nature.